Mismatch in sexual dimorphism of developing song and song control system in blue-capped cordon-bleus, a songbird species with singing females and males - Lobato, Muriele; Vellema, Michiel; Gahr, Christoph; Leitão, Albertine; de Lima, Silene M. A.; Geberzahn, Nicole; Gahr, Manfred (Frontiers in Ecology and Evolution, 2015)
Brain song control regions of adult passerine birds are sexually dimorphic in species such as the zebra finch (Taeniopygia guttata) in which males sing whereas females do not. In many tropical bird species, however, females sing as well. Here we study for the first time the ontogeny of the song control system and the song in a species, in which both male and female sing regularly. In blue-capped cordon-bleus (Uraeginthus cyanocephalus), a distant relative of the zebra finch, both males and females start singing at around 30-40 day post-hatching (dph). First we quantified that sex-specific differences in song features emerged only in adulthood, after 250 dph of age: Adult females sang complex songs, which were slightly shorter and contained fewer syllables as compared to the males. Second, the development of forebrain song control regions HVC (proper name) and RA (nucleus robustus arcopallii) of blue-capped cordon-bleus was quantified in both sexes at 20, 30, 50, 100, 150, 250 dph as well as in old adults. The volume and neuron numbers of the HVC and RA were sexually dimorphic throughout the entire development and remained sexually dimorphic in adulthood. Since singing developed in a non sex-specific way until 250 dph, neural sex differences to a large extend precede the behavioral (song) sex differences. This suggests that these neuroanatomical sex differences are not causally related to the sexual differentiation of song patterns in this species.